Revealing Novel Source of Breast Cancer Inhibitors from Seagrass Enhalus acoroides: In Silico and In Vitro Studies - Yan Wisnu Prajoko; Faqrizal Ria Qhabibi; Timothy Sahala Gerardo; Kanandya Kizzandy; Krisanto Tanjaya; Sebastian Emmanuel Willyanto; Happy Kurnia Permatasari; Reggie Surya; Nelly Mayulu; Nurpudji Astuti Taslim; Raymond Rubianto Tjandrawinata; Rony Abdi Syahputra; et al. (Molecules, 2024)
Enhalus arcoides is a highly beneficial type of seagrass. Prior studies have presented proof of the bioactivity of E. acoroides, suggesting its potential to combat cancer. Therefore, this study aims to delve deeper into E. acoroides bioactive molecule profiles and their direct biological anticancer activities potentials through the combination of in-silico and in-vitro studies. This study conducted metabolite profile analysis on E. acoroides utilizing HPLC-ESI-HRMS/MS analysis. Two extraction techniques, ethanol and hexane, were employed for the extraction process. Furthermore, the in-silico study was conducted using molecular docking simulations on the HER2, EGFR tyrosine kinase and HIF-1α protein receptor. Afterward, the antioxidant activity of E. acoroides metabolites was examined to ABTS, and the antiproliferative activity was tested using an MTT assay. An in-silico study revealed its ability to combat breast cancer by inhibiting the HER2/EGFR/HIF-1α pathway through molecular docking. In addition, the MTT assay demonstrated that higher dosages of metabolites from E. acoroides increased the effectiveness of toxicity against cancer cell lines. Additionally, the study demonstrated that the metabolites possess the ability to function as potent antioxidants, effectively inhibiting a series of carcinogenic mechanisms. Ultimately, this study showed a new approach to unveiling the E. acoroides metabolites’ anticancer activity through inhibiting HER2/EGFR/HIF-1α receptors, with great cytotoxicity and a potent antioxidant property to prevent a carcinogenic cascade.